Correlation of Laboratory Management With Students’ Ability To Monitoring Nutritional Status - Desi Dedi Arisandi; Zakiyuddin Zakiyuddin; Arif Iskandar; Fedia Rizkita (Universitas Teuku Umar, 2022)
The laboratory can act as its function if it is managed properly so that it contributes to the effectiveness of students in understanding a lesson. The purpose of the study was to determine the correlation between laboratory management and students' ability to monitor nutritional status. This study uses quantitative research methods with correlational analysis using a Likert scale. The research locus is the Nutrition Laboratory of the Faculty of Public Health, Teuku Umar University. The sample used was a total sampling of a population of 65 students majoring in Nutrition who took the nutritional status monitoring course in 2022. The data were analyzed using a questionnaire analysis test and an analysis of the student's ability to monitor nutritional status. To test the truth of the hypothesis, a computerized rank spearmen correlation test was used with the help of SPSS software version 25. The results showed that 94% of students thought that the laboratory management activities of the Faculty of Public Health, Teuku Umar University were very good. Almost all nutrition students have very high scores (92%) while the rest have high scores (1%), moderate scores (5%), and low scores (2%). Based on the spearmen rank test, a significance value of (0.000) < alpha (0.05) was obtained with a correlation coefficient of 0.442. In conclusion, there is a correlation between laboratory management and the ability of students to monitor nutritional status with a currently level of relationship strength.